Our first experience with combined positron emission tomography and computed tomography (PET/CT) in patients with gastric cancer - Kula, Zbigniew; Szefer, Jarosław; Pietrzak, Tomasz; Zuchora, Zdzisław (Contemporary Oncology/Współczesna Onkologia, 2005)
The application of positron emission tomography (PET) using F-18-fluorodeoxyglucose (FDG) is the latest method of functional imaging of the human body, trunk, or selected human organs. In oncology diagnostics, it uses the enlarged uptake of positron radiotracer, by cancer cells. FDP-PET scanning and computed tomography (CT) offer wider diagnostic possibilities. FDG-PET and PET/CT are used more and more frequently in patients having gastrointestinal malignancies, especially colorectal, esophageal and pancreas carcinoma. This paper is a retrospective assessment of PET/CT fusion images in 22 patients with gastric cancer. The reason for this diagnosis in 12 out of 22 patients was suspicion of recurrent gastric cancer after surgery, in 5 cases - cancer progression assessment before surgery, in 4 – assessment after the end of treatment, in one of them - assessment of chemotherapy efficacy. Focal increased FDG uptake was found in 9 patients. In 7 patients recurrent gastric cancer after treatment was observed and in one patient - primary gastric cancer. Correctness of PET/CT scan was assessed on the basis of clinical remarks of patients, additional examination (chest roentgenogram, abdomen cavity ultrasonography and CT, histopathological examination) and intraoperative examination. In 9 patients PET/CT was true positive, in 3 patients - false negative, and in all the other – true negative. A correlation between scan results and a histopathological structure was noticed. PET/CT image in selected patients with gastric cancer provides a useful diagnostic method of primary staging and detection of a recurrent disease, restaging and treatment monitoring. First primary experiences justify the assessment of PET/CT findings in patients with gastric cancer for a prospective study.